1986
DOI: 10.1007/bf00043917
|View full text |Cite
|
Sign up to set email alerts
|

The influence of initial sucrose and nitrate concentrations on the growth of Cinchona ledgeriana cell suspension cultures and the production of alkloids and anthraquinones

Abstract: The influence of initial concentrations of two of the major medium components, sucrose and nitrate, on the growth and the production of alkaloids and anthraquinones in cell suspension cultures of Onchona ledgeriana Moens was studied. It was found that maximum growth and maximum alkaloid yield were obtained with a B smedium containing the normal level of nitrate and 4% sucrose, whereas the anthraquinone yield was maximum at 8% sucrose at the normal level of nitrate. Maximum contents of secondary metabolites, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
5

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 14 publications
(8 reference statements)
1
3
0
5
Order By: Relevance
“…The specific growth rates for Catharanthus roseus and Nicotiana tabacum cell cultures are 0.35 -0.68 day-' and 0.28 day -l, respectively (Drapeau et al, 1986;Sahai and Shuler, 1984). However, the growth rate of our strawberry cell cultures was similar to that obtained with Cinchona ledgetiuna, which has a specific growth rate between 0.11 and 0.16 day-l (Wijnsma et al, 1986).…”
Section: Resultssupporting
confidence: 64%
“…The specific growth rates for Catharanthus roseus and Nicotiana tabacum cell cultures are 0.35 -0.68 day-' and 0.28 day -l, respectively (Drapeau et al, 1986;Sahai and Shuler, 1984). However, the growth rate of our strawberry cell cultures was similar to that obtained with Cinchona ledgetiuna, which has a specific growth rate between 0.11 and 0.16 day-l (Wijnsma et al, 1986).…”
Section: Resultssupporting
confidence: 64%
“…Studies showed that the sucrose could influence secondary metabolites production in cell and organ cultures [21][22]. The results of many investigations have concluded that the increase of sucrose within certain limits leads to increased production of alkaloids in tissue cultures of various plants [23][24][25]. Matsumoto et al [26] reported that increase of sucrose in the tissue culture medium leads to an increase of phytochemicals.…”
Section: Resultsmentioning
confidence: 99%
“…Produksi kuinolin dari kultur in vitro tanaman kina telah dilakukan menggunakan kalus (Staba & Chung, 1981), suspensi sel (Anderson et al, 1982;Koblitz et al, 1983;Wijnsma et al, 1986) dan akar transform (Hamill et al, 1989;Geerlings et al, 1999;Toruan-Mathius et al, 2004). Produksi alkaloid dari kultur in vitro tersebut beragam dan masih sangat rendah, kurang dari 1 mg/g bobot kering.…”
Section: Pendahuluanunclassified
“…Dari hasil penelitian ini persentase kontaminasi eksplan ex vitro sekitar 40% bila tanaman sumber eksplan diletakkan terlebih dahulu di rumah kaca, sedangkan kontaminasi pada eksplan asal tanaman in vitro sekitar 10%. Untuk menginduksi kalus tanaman kina, MS merupakan medium yang paling banyak digunakan walaupun medium B5 kadangkala digunakan juga (Scragg et al, 1986;Wijnsma et al, 1986). Salah satu masalah dalam induksi kalus dari tanaman kina adalah terjadinya pencokelatan (browning) yang berlangsung relatif cepat.…”
Section: Induksi Kalusunclassified
See 1 more Smart Citation